The Future is Fixed - Crow, Jason (ARCC Conference Repository, 2014)
Isaac Asimov once commented that nothing ever changed in the science fiction of the former Soviet Union. Any suggestion that the future might be different brought the risk of censorship. Soviet cinema could note take place in time. As a result in films like Mechte Navstrechu (1963) erratic and discontinuous plot devices allowed a vision of the future in which no alteration of the present occurred. The future remained the same as the present: No change was allowed. Martin Heidegger made a similar observation about the inability to change as a key characteristic of any environment in his 1929-30 lectures on metaphysics. Heidegger differentiated between the environments of the animal and of the human by noting that both were trapped in a set of fixed relationships. However, the human could imagine the possibility of changing the environment. Heidegger thus defined humanity by a capacity not to change but to envision the present differently. Read closely, these transitional lectures reveal the inability of technology to offer anything new. Curiously, Soviet-era science fiction worked critically within a previously established future condition. These fictions deployed the future as a signpost from which detours could be taken. Breaking the narrative allowed for seemingly unimaginable alternatives to be presented without truly effecting any change. The future was never a goal to be obtained within the context of these films. It was an orienting distraction, and as such it offers a new way of thinking about the intent of computation for architecture. If the image, model, simulation are conceived as orienting distractions from the ensnarement of time” Î±Ï‡ÏÎ¿Î½Î¯Î± ”can they be used to displace the future from the present and restore critique to the architectural utopia?